Decisive factors to mortality of micro and small companies in the metropolitan area of Florianopolis from the standpoint of the accountant - Nascimento, Marcelo (2013)
The objective of this paper is to analyze under the accountant perspective the determining factors for early mortality of micro and small enterprises in the city of Florianopolis, Brazil. In order to learn more about the aspects that lead companies to succumb, it was conducted a quantitative research. For data collection, a questionnaire was applied to 141 accountants from the metropolitan region of Florianopolis. It was possible to identify that most of the factors cited by the specialized literature is equally important from the accountant perspective. Even so, two factors cited in the specialized literature were not crucial under the perspective of the accountant to the failure of MSE, namely, the education level of the entrepreneur and the tax burden.